Literature Study: Correlation of Self-Regulation with Social Behavior in Children with Special Needs - Aqilah, Thalsa Syahda; Irvan, Muchamad; Sunandar, Asep; Huda, Abdul (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
Children with special needs have atypical development that is different from children in general. They need to face various types of obstacles in carrying out their functions as humans. One of these obstacles is social development which has an impact on the emergence of problematic social behavior. The presence of these disorders is suspected to be connected to their inadequate self-regulation. This study aims to provide a comprehensive view of the correlation between self-regulation and social behavior in children with special needs based on scientific evidence. The method used is a literature review. The results of the study indicate that the social behavior of children with special needs which is often hampered has a correlation with self-regulation which is connected through executive function disorders and theory of mind and can be exacerbated by the presence of comorbid conditions.